Real‐Time, In Vivo Measurement of Protein Kinase A Activity in Deep Brain Structures Using Fluorescence Lifetime Photometry (FLiP). Issue 10 (18th October 2021) - Lodder, Bart; Lee, Suk Joon; Sabatini, Bernardo L.
Abstract: The biochemical state of neurons, and of cells in general, is regulated by extracellular factors, including neurotransmitters, neuromodulators, and growth hormones. Interactions of an animal with its environment trigger neuromodulator release and engage biochemical transduction cascades to modulate synapse and cell function. Although these processes are thought to enact behavioral adaption to changing environments, when and where in the brain they are induced has been mysterious because of the challenge of monitoring biochemical state in real time in defined neurons in behaving animals. Here, we describe a method allowing measurement of activity of protein kinase A (PKA), an important intracellular effector for neuromodulators, in freely moving mice. To monitor PKA activity in vivo, we use a genetically targeted sensor (FLIM‐AKAR) and f luorescence li fetime p hotometry (FLiP). This article describes how to set up a FLiP system and obtain robust recordings of net PKA phosphorylation state in vivo. The methods should be generally useful to monitor other pathways for which fluorescence lifetime reporters exist. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Building a FLiP system Basic Protocol 2 : FLIM‐AKAR viral injection and fiber implantation for FLiP measurement Basic Protocol 3 : Performing measurements using FLiP